-2(2n+1)=4

Simple and best practice solution for -2(2n+1)=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(2n+1)=4 equation:


Simplifying
-2(2n + 1) = 4

Reorder the terms:
-2(1 + 2n) = 4
(1 * -2 + 2n * -2) = 4
(-2 + -4n) = 4

Solving
-2 + -4n = 4

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + -4n = 4 + 2

Combine like terms: -2 + 2 = 0
0 + -4n = 4 + 2
-4n = 4 + 2

Combine like terms: 4 + 2 = 6
-4n = 6

Divide each side by '-4'.
n = -1.5

Simplifying
n = -1.5

See similar equations:

| 2x^2+3=-4x | | 0.2(30-10x)=0.6(4x+2) | | 6(p-1)=3p | | -4x+15=11 | | 7x-5=7x+5 | | -4x+7=-1 | | z^2+12x+31=0 | | 5x^2=36x+32 | | 6(4z-1)-4(z+2)=17(z+1) | | 4y+y=6 | | c+5= | | .00000000000112=4x^3+5.6x^2 | | (x-1)(x+2)= | | (x+4)(x+1)= | | 15x+12y=0 | | 8=D | | 2x/5=-3+7 | | 4z^2+32z+63=0 | | 9n+72= | | 14y^2-15y+4=0 | | 3h=2h-8 | | 6(a+2)= | | 0.28x-0.75x=-13 | | 49s^2-9=0 | | x^2-16x+66=0 | | 1.5x+0.6x=13 | | 7.2x-3.7=17.9 | | 287-7x=38x+22 | | 3r^2+2r-21= | | 0.5x-0.2x=3 | | 4y=7 | | 18x-9+3z=18 |

Equations solver categories